Justice League - Snyder, Scott 1976-; Tynion, James IV 1987- (DC Comics, 2018)
"The League was forced to make an impossible decision ... and now its time to face the consequences! The returning Martian Manhunter struggles to protect the team from an incoming threat that will shatter the world as they know it, while a familiar face strikes out on a dark path... Spinning out of the cataclysmic events of Dark Nights: Metal and the universe-defining No Justice, the core members of the Justice League--Superman, Batman, Wonder Woman, Aquaman, The Flash and more--are finally reunited for an adventure for the ages!"--
Keywords: Batman -- Fiktive Gestalt; Superman -- Fiktive Gestalt; Wonder Woman -- Fiktive Gestalt; Aquaman -- Fiktive Gestalt; Justice League of America; Comic